1999
DOI: 10.1055/s-1999-2976
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Markovnikov Addition of Thiols Across Double Bonds Catalyzed by H-Rho-Zeolite

Abstract: A variety of olefins react with thiols in the presence of a catalytic amount of H-Rho-zeolite to afford the corresponding antiMarkovnikov addition products in good to excellent yields.The last few years have witnessed a considerable upsurge of interest in the area of zeolite induced organic transformations. 1 In a series of publications from our group, 2 we have exploited the catalytic potential of zeolites for various organic synthetic transformations, e.g. thioacetalization of carbonyl compounds, sulfoxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 1 publication
0
12
0
3
Order By: Relevance
“…However, this strategy is limited to aromatic‐substituted unsaturated substrates or those activated for Michael‐type additions, and sometimes requires a stoichiometric amount of base 31. More recently, several methods, including the use of zeolites,32 nanoparticles,33 ionic liquids,34 and other supports have been developed, especially for alkynes, in an attempt to improve the recyclability of the reaction 35. In this respect, special attention has been paid to the use of water as a green solvent in hydrothiolation 36.…”
Section: Non‐metal‐mediated Hydrothiolationmentioning
confidence: 99%
“…However, this strategy is limited to aromatic‐substituted unsaturated substrates or those activated for Michael‐type additions, and sometimes requires a stoichiometric amount of base 31. More recently, several methods, including the use of zeolites,32 nanoparticles,33 ionic liquids,34 and other supports have been developed, especially for alkynes, in an attempt to improve the recyclability of the reaction 35. In this respect, special attention has been paid to the use of water as a green solvent in hydrothiolation 36.…”
Section: Non‐metal‐mediated Hydrothiolationmentioning
confidence: 99%
“…Allerdings ist diese Strategie auf ungesättigte Substrate mit aromatischen Substituenten oder für Michael‐Additionen aktivierte Substrate beschränkt und erfordert manchmal stöchiometrische Mengen der Base 31. Vor kurzem wurden besonders für Alkine einige Methoden entwickelt, einschließlich der Verwendung von Zeolithen,32 Nanopartikeln,33 ionischen Flüssigkeiten34 und anderen Trägermaterialien, um die Wiederverwertbarkeit des Reaktionssystems zu verbessern 35. Dabei wurde besonders auf die Verwendung von Wasser als umweltfreundlichem Lösungsmittel für die Hydrothiolierung geachtet 36.…”
Section: Nicht‐metallvermittelte Hydrothiolierungunclassified
“…In all cases listed in Table 1, the addition reaction proceeded with excellent regio-and stereoselectivity to provide only the E isomer of the anti-Markovnikov adduct 3. Although the solid supports such as H-Rho-Zeolite and Montmorillonite K 10 are known to catalyze regioselectively the addition of thiols to olefins in high yields in an anti-Markovnikov or a Markovnikov manner [35,36], no the addition of thiols to alkynes catalyzed by the solid supports has been reported until now. We also found that the addition reaction of thiols to alkynes did not occur in the presence of MCM-41 or MCM-41-2P support without rhodium.…”
Section: Preparation Of Mcm-41-2p-rhcl(pph 3 )mentioning
confidence: 99%